2011
DOI: 10.1080/09540121.2010.525789
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a nutritional counseling program on prevention of HAART-related metabolic and morphologic abnormalities

Abstract: The advent of highly active antiretroviral therapy (HAART) improved HIV infection prognosis. However, adverse metabolic and morphologic effects emerged, highlighting a lack of investigation into the role of nutritional interventions among this population. The present study evaluated the impact of a nutritional counseling program on prevention of morphologic and metabolic changes in patients living with HIV/AIDS receiving HAART. A 12-month randomized clinical trial was conducted with 53 adults of both genders i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 33 publications
2
46
1
Order By: Relevance
“…Participants in the intervention group decreased their intake of carbohydrates by 24 weeks of follow-up (−38.3 ± 16.7 g/day, p=0.03). In contrast to our study, a 12-month randomized controlled trial in Brazil of 53 HIV-infected patients receiving ART showed a reduction in fat consumption at the end of the study, but no significant differences in lipid levels between the intervention and control groups (Almeida, Segurado, Duran, & Jaime, 2011). Similar to our findings, they demonstrated no significant changes in waist circumference or blood pressure between groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Participants in the intervention group decreased their intake of carbohydrates by 24 weeks of follow-up (−38.3 ± 16.7 g/day, p=0.03). In contrast to our study, a 12-month randomized controlled trial in Brazil of 53 HIV-infected patients receiving ART showed a reduction in fat consumption at the end of the study, but no significant differences in lipid levels between the intervention and control groups (Almeida, Segurado, Duran, & Jaime, 2011). Similar to our findings, they demonstrated no significant changes in waist circumference or blood pressure between groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Twenty‐seven RCTs met the eligibility criteria and were included in the review, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…After one year, only 21% of patients who received nutritional counseling had lipid profiles compatible with dyslipidemia compared with 68% of controls. In another 12-month randomized clinical trial with 53 adults on HAART, an individualized nutritional counseling program based on a client-centered approach led to a reduction in fat consumption and increase in fiber intake [82]. These dietary changes did not translate into improved biochemical metabolic status.…”
Section: Nutritional Interventionsmentioning
confidence: 99%